Detailed Spatial Planning (RDTR) Policy for The Arrangement of Wifi Network Aerial Cables in The Special Region of Yogyakarta - Aco, Faizal (Kemudi, 2024)
Technological developments provide more convenience for the community. This is because almost all aspects of human life are inseparable from the touch of technology. The technology that is currently developing rapidly is the internet, because the internet is the most complete source of information that is easy to obtain. With the internet it will be very easy and fast to get the latest information from all corners of the country, both domestically and abroad. The type of this research is descriptive qualitative research, namely data collection research by interviewing and written data using descriptive qualitative methods. Data collection techniques used are observation, interviews with a number of informants, and from certain document sources related to research. Installing WiFi network poles sometimes disrupts the activities of local communities, it has been proven that many network poles are planted very close to residential areas. forexample in the Sedayu area, Kulonprogo Regency, the Seturan Depok area, Sleman Regency, the Tamanan area in Bantul Regency. It has been observed that in the area around Sedayu, Bantul Regency, telecommunications networks, especially Fiber Optic (FO) lines, are increasingly filling street corners and cities, this is because during the Covid-19 pandemic, many people installed WiFi networks that were connected to people's homes, so the growth was very high fast. Apart from that, operators are also expanding their networks to reach customers everywhere. From other sources, conditions like this are commonplace everywhere, the number of customers and new networks to customers is increasing so that this is one of the factors for service providers without looking at the right environmental location for installing WiFi cable poles.